Early patient and liver allograft outcomes from donation after circulatory death donors using thoracoabdominal normothermic regional: a multi-center observational experience - Brubaker, Aleah L.; Taj, Raeda; Jackson, Brandon; Lee, Arielle; Tsai, Catherine; Berumen, Jennifer; Parekh, Justin R.; Mekeel, Kristin L.; Gupta, Alexander R.; Gardner, James M.; Chaly, Thomas; Mathur, Amit K.; et al. (Frontiers in Transplantation, 2023)
Background: Donation after circulatory death (DCD) liver allografts are associated with higher rates of primary non-function (PNF) and ischemic cholangiopathy (IC). Advanced recovery techniques, including thoracoabdominal normothermic regional perfusion (TA-NRP), may improve organ utilization and patient and allograft outcomes. Given the increasing US experience with TA-NRP DCD recovery, we evaluated outcomes of DCD liver allografts transplanted after TA-NRP. Methods: Liver allografts transplanted from cDCD donors after TA-NRP were identified from 5/1/2021 to 1/31/2022 across 8 centers. Donor data included demographics, functional warm ischemic time (fWIT), total warm ischemia time (tWIT) and total time on TA-NRP. Recipient data included demographics, model of end stage liver disease (MELD) score, etiology of liver disease, PNF, cold ischemic time (CIT), liver function tests, intensive care unit (ICU) and hospital length of stay (LOS), post-operative transplant related complications. Results: The donors’ median age was 32 years old and median BMI was 27.4. Median fWIT was 20.5 minutes; fWIT exceeded 30 minutes in two donors. Median time to initiation of TA-NRP was 4 min and median time on bypass was 66 minutes. The median recipient listed MELD and MELD at transplant were 22 and 21, respectively. Median allograft CIT was 292 minutes. The median length of follow up was 257 days. Median ICU and hospital LOS were 2 and 7 days, respectively. Three recipients required management of anastomotic biliary strictures. No patients demonstrated IC, PNF or required re-transplantation. Conclusion: Liver allografts from TA-NRP DCD donors demonstrated good early allograft and recipient outcomes.